Informe pasantía de investigación: Prospectiva de los perfiles ocupacionales de las Industrias Culturales y Creativas: Industria Audiovisual Bogotá (2022)
This research identifies the occupational profiles of the cultural and creative industries, specifically the audiovisual industry in the city of Bogota, using a qualitative methodology designed by SENAI (Serviço Nacional de Aprendizagem Industrial), in Brazil and validated by the Ministry of Labor in Colombia, based on semi-structured interviews with specialists dedicated to audiovisual production in the city and subsequently validated in a focus group formed by themselves